Clinical Heterogeneity of Immune Dysregulation, Polyendocrinopathy, Enteropathy, X-Linked Syndrome: A French Multicenter Retrospective Study. Issue 10 (October 2018) - Duclaux-Loras, R.; Charbit-Henrion, F.; Neven, B.; Nowak, J.; Collardeau-Frachon, S.; Malcus, C.; Ray, P.; Moshous, D.; Beltrand, J.; Goulet, O.; Cerf-Bensussan, N.; Lachaux, A.; et al.
Abstract Objective Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is an autoimmune disease caused by mutations in the forkhead box protein 3 gene (FOXP3 ), which encodes a key regulator of immune tolerance. The aim of this study was to describe the clinical heterogeneity of the disease in a national French cohort. Methods Multicenter retrospective study of patients diagnosed with IPEX syndrome caused by mutations inFOXP3 . Results Thirty children from 26 families were included. Age at disease onset (median [first to third quartile]) was 1.5 mo [0–84] and at death 3.5 years [0–10.5] (n = 15) indicating a high heterogeneity. Initial presentation was diarrhoea (68%), type 1 diabetes (T1D; 25%), skin lesions (7%) and nephropathy (3%). During the course of the disease the following main symptoms were observed: diarrhoea (100%), skin lesions (85%), T1DM (50%), severe food allergies (39%), haematological disorders (28%), nephropathies (25%), hepatitis (14%) as well as the presence of a variety of autoantibodies. Immunosuppressive mono- or combination therapy led to improvement in eight children. Three boys displayed a stable disease course without any immunosuppressive medication. Overall 10-year survival rate was 43% (42% in transplanted patients and 52% in patients on immunosuppressive therapy). Five out of 22 identifiedFOXP3 mutations have not been described yet: c.−23 + 1G > A, c.−23 + 5G > A, c.264delC, c.1015C > T and c.1091A > G. The first two produced atypical, attenuated phenotypes. Missense and frameshift mutations affecting the forkhead domain were associated with poor survival (Gehan–Wilcoxonp = 0.002). Conclusion The broad phenotypic heterogeneity of IPEX raises questions about modifying factors and justifies earlyFOXP3 sequencing in suspected cases.